The Role of Spiritual Leadership on Teachers' Professional Ethics with Affective Commitment and Workplace Spirituality as Mediators - Lukas Purwoto; Yohanes Adeyudha Subhakti (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Teachers are often faced with various situations and challenges that can affect their professional ethics. By implementing strong ethics, teachers not only teach but also educate the younger generation to be intellectually and morally mature. Therefore, schools require a climate and paradigm that supports the maintenance of ethical values and behavior in their teachers, which can be realized through spiritual leaders. This study aims to examine the influence of spiritual leadership on teachers' professional ethics and investigate mediation through affective commitment and workplace spirituality. This study applied a quantitative approach and was conducted by distributing questionnaires to 220 school teachers. Data analysis was conducted using PLS-SEM analysis. The result of the study indicate that teachers' professional ethics can be pursued by leaders by fulfilling teachers' needs for good spirituality through participation and membership to create a vision and values that guide teachers in maintaining their professional ethical behavior. In addition, the mechanism of this relationship is realized in schools through increasing affective commitment and workplace spirituality. The implication of the result of this study is that school leaders can use spiritual leadership to develop teachers in improving professional ethics.